Prediksi Konsentrasi Klorofil-a Menggunakan Data Citra Satelit Sentinel-2A di Waduk Jatiluhur Kabupaten Purwakarta - Arip Rahman; Lismining Pujiyani Astuti; Andri Warsa; Agus Arifin Sentosa (BRIN Publishing (Penerbit BRIN), 2022)
Lakes, reservoirs, and rivers are among the most changing ecosystems on the earth’s surface. Chlorophyll-a as the main pigment in phytoplankton is often used to describe the water quality of lake and reservoirs and as an important element that indicates the tropical status of a waters. Spatial and temporal changes in algae blooms in a lake make it difficult to use in situ monitoring. The aim of the study is to predict the concentration of chlorophyll-a in Jatiluhur Reservoirs. The data used in this study were chlorophyll-a data from in situ measurements and satellite data Sentinel-2A. The method to obtain the value of the concentration of chlorophyll-a are an empirical and semi-analytical method. The empirical method is carried out by correlating in situ data with ratio of band 5 (red edge) and band 4 (red) (B5/B4). While the semi-analytical method is carried out by analyzing the Case 2 Regional Coast Colour (C2RCC) algorithm that integration in Sentinel Application Platform (SNAP) software. Correlation between in situ data and prediction of chlorophyll-a data has a strong relationship with the coefficient of determination R2=0.67 (in situ data with ratio prediction data) and R2=0.56 (in situ data with C2RCC prediction data). Based on this, remote sensing data on Sentinel-2A imagery with the application of several algorithms, can be used to support water quality monitoring activities in lakes and reservoirs, especially chlorophyll-a.